Anticancer peptides derived from Supermeal worm, Zophobas morio - Chowdhury, Silvia; Yusof, Faridah; Sulaiman, Nadzril; Faruck, Mohammad Oamylasemer (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Cancer is an extremely complicated disease and still presents enormous challenges in the medical world. In recent decades, doctors and researchers were able to find some potential compounds that may be able to treat cancer, but due to the difficulties commercialization poses like mass production, high cost of clinical trials and expensive formulation, not many of these compounds have reached the market. Currently, the search for anticancer compounds has garner a lot of interest, especially in finding them from the natural sources. In this study, compounds, supposedly peptides, extracted from cheap, easily maintained Supermeal worm (Zophobas morio) using two types of acidified organic solvent, ethanol and isopropanol, were shown to inhibit the growth of MCF-7, a breast cancer cell line. A comparative study of the effects were carried out on Vero cell, a normal cell line. Results showed that, the two type of extracts inhibits growth of MCF-7 cell at varying degrees, but on the other hands, have much less effect on Vero cell. Extracts, identified using Raman Spectroscopy shows peaks at 1349 cm-1 , 944 cm-1 and 841 cm-1 indicating the presence of Tyr, Try and Gly. In addition, UV-vis analysis showed peaks in the range of 260 to 280 nm, inferring the presence of Tyr and Try, whereas the highest peak, 3.608 at 230 nm indicates the presence of peptide bond. All the results of analyses implied that the anticancer compounds contain peptides